Edukasi Menggunakan Booklet untuk Membantu Keluarga Mencegah Penyakit Menular pada Lansia - Rahayu, Dian Yuniar Syanti; Usman, Reni Devianti; Umar , Nurlailah; Putri, Dwi Purnama (Health Information : Jurnal Penelitian, 2022)
The elderly often have mild levels of immunosuppression, age-related organ changes, comorbidities, weakness, malnutrition, functional dysfunction, all of which affect the prognosis of geriatric patients with infectious diseases. Vulnerability to infectious diseases in the elderly can have an impact on the complexity of health problems experienced by the elderly and even increase the risk of death, so preventing infectious diseases in the elderly is a priority. The family is the main source of support in the care of the elderly, because the family is the person who lives with the elderly. Knowledge is a resource that can support behavior, including the prevention of infectious diseases. Education is the main means in increasing family knowledge for the prevention of infectious diseases in the elderly. Booklet media is one of the educational media that contains the information needed and its use is easy and can be used as needed. This study aims to identify the effect of education with booklet media on the ability of families to prevent infectious diseases in the elderly in the working area of ??Abeli ??Health Center. The study method used is a quasi-experimental, pre-test and post-test design. The population and sample in this study were families who had elderly, the technique of determining the sample was using the simple random sampling method. Each family who is willing to become a respondent is represented by 1 person in the family, the total number of respondents is 55 people. The results showed that there was an effect of providing education using booklets on the ability of families to prevent the transmission of infectious diseases to the elderly (P value = 0.000). Education for elderly families by using booklets can help families prevent infectious diseases in the elderly.